Distinct etiology of chronic inflammation – implications on degenerative diseases and cancer therapy - Maddipati, Krishna Rao (Frontiers in Immunology, 2024)
Acute inflammation is elicited by lipid and protein mediators in defense of the host following sterile or pathogen-driven injury. A common refrain is that chronic inflammation is a result of incomplete resolution of acute inflammation and behind the etiology of all chronic diseases, including cancer. However, mediators that participate in inflammation are also essential in homeostasis and developmental biology but without eliciting the clinical symptoms of inflammation. This non-inflammatory physiological activity of the so called ‘inflammatory’ mediators, apparently under the functional balance with anti-inflammatory mediators, is defined as unalamation (un-ala-mation). Inflammation in the absence of injury is a result of perturbance in unalamation due to a decrease in the anti-inflammatory mediators rather than an increase in the inflammatory mediators and leads to chronic inflammation. This concept on the etiology of chronic inflammation suggests that treatment of chronic diseases is better achieved by stimulating the endogenous anti-inflammatory mediators instead of inhibiting the ‘inflammatory’ mediator biosynthesis with Non-Steroidal Anti-Inflammatory Drugs (NSAIDs). Furthermore, both ‘inflammatory’ and anti-inflammatory mediators are present at higher concentrations in the tumor microenvironment compared to normal tissue environments. Since cancer is a proliferative disorder rather than a degenerative disease, it is proposed that heightened unalamation, rather than chronic inflammation, drives tumor growth. This understanding helps explain the inefficacy of NSAIDs as anticancer agents. Finally, inhibition of anti-inflammatory mediator biosynthesis in tumor tissues could imbalance unalamation toward local acute inflammation triggering an immune response to restore homeostasis and away from tumor growth.